El desarrollo socio afectivo en los niños de 4 años - Quispilema López, Sara Elizabeth (2023)
This work is based on fulfilling the objective of identifying the socio-affective development of 4-year-old children. The study was implemented with a mixed approach through surveys and interviews with teachers and parents to find out the different ways in which they develop affectivity in children of this age. The sample was prepared by eleven students, seventeen parents, two teachers and a director. Socio-affective development in 4-year-old children is a crucial age in their growth and becomes an important stage in their development, since they experience significant changes in their emotional and social skills. During this period, children begin to develop a greater understanding of themselves and others, which allows them to form more complex relationships and express their emotions more intensely. At age 4, children show increased interest in interacting with peers and adults, beginning to understand and apply basic social rules, such as taking turns to speak and sharing. Although they may still show moments of selfishness, they are learning to cooperate and play in a group knowing their emotions.